Implementation Of Data Mining In Digital Marketing Of Knit Bag Msmes West Bandung District - Saepulloh, Yusep; Amirulloh, Moch Mumin; Juliane, Christina (International Journal of Science Education and Technology Management, 2024)
Knitted Bag Micro, Small and Medium Enterprises MSMEs in West Bandung Regency face challenges in exploiting the potential of the digital market. This research aims to apply data mining techniques to understand consumer patterns and increase the effectiveness of digital marketing strategies. In the methods section, the approach used in the clustering analysis is explained in detail. The data used, the variables observed, as well as the clustering techniques and statistical tests applied are described. In addition, the data processing and analysis procedures carried out are also explained to provide a clear understanding of the research methodology. This section presents the results of the clustering analysis and statistical tests performed. This includes the results of the clustering process using K-Means, the resulting cluster centers, as well as the results of the variance test showing the differences in means between cluster groups. Patterns in the data, differences between cluster groups, as well as the potential use of analysis results for developing marketing strategies and customer management are discussed in depth. This research succeeded in grouping customer data into five different clusters based on observed variables. Clustering analysis has helped in understanding patterns in data and identifying different customer groups. The implications of these findings for customer management and marketing strategy development are discussed, and suggestions for further research and development are provided.